Interfacial engineering of a polymer–MOF composite by in situ vitrification. Issue 25 (13th March 2020) - Lin, Rijia; Hou, Jingwei; Li, Mengran; Wang, Zhanke; Ge, Lei; Li, Shichun; Smart, Simon; Zhu, Zhonghua; Bennett, Thomas D.; Chen, Vicki
Abstract : In situ vitrification of MOF within polymer can rigidify the polymer chains and remove interfacial defects, leading to a significantly enhanced membrane selectivity. Abstract : Non-stoichoimetric crystalline ZIF-62 was used as the filler for a 6FDA-DAM polyimide-based composite membrane. In situ melting and vitrification of ZIF-62 was then performed, to yield the ZIF-62 glass phase (ag ZIF-62), within the polymer matrix. Focus ion beam scanning electron microscopy (FIB-SEM), thermal characterisation and membrane separation tests demonstrate the filling of voids at the MOF/polymer interface from the liquid phase of ZIF-62.